A - Risen, Clay (John Wiley & Sons, 2009)
A few hours after Rev. Martin Luther King, Jr. was assassinated at a Memphis motel, violent mobs had looted and burned several blocks of Washington a few miles north of the White House, centered around the U Street commercial district. Quick action by D.C. police quelled the violence, but shortly before noon the next day, looting and arson broke out anew -- not just along U Street, but in two other commercial districts as well